Improving dispersion stability of hydrochloric acid hydrolyzed cellulose nano-crystals. (15th October 2019) - Shang, Zhen; An, Xingye; Seta, Frederikus Tunjung; Ma, Mingshuai; Shen, Mengxia; Dai, Lin; Liu, Hongbin; Ni, Yonghao
Graphical abstract: Highlights: HCNC can be modified and well dispersed in aqueous system by CTAB adsorption. CTAB can improve HCNC dispersion stability by providing effective steric barriers. CTAB at high concentration (＞0.5 mM) will form micelles and cause HCNC aggregation. CTAB adsorption would maintain the crystalline structure and thermal stability of HCNC. Abstract: Cellulose nano-crystals (CNC) have attracted great interests as a novel nanostructured material in recent years, thanks to their excellent mechanical properties, high surface area and lightweight and biocompatibility etc. Due to its low charged group content, CNC prepared from the hydrochloric acid hydrolysis has poor dispersibility in water, which hinders its further applications. In this work, well-dispersed cellulose nano-crystals are successfully prepared using a two-step method, consisting of hydrochloric acid hydrolysis, followed by adsorption of hexadecyl trimethyl ammonium bromide (CTAB) onto CNC. Results show that CTAB at a low concentration (0.13–0.47 mM) provides effective steric barriers to minimize the CNC aggregation, which is supported by TEM images and particle size distribution of CNC. At high CTAB concentrations (>0.5 mM), CNC aggregation occurs, which is due to the "bridging" effect of CTAB.